Editoriale/Editorial/Éditorial/Editorial - (a cura di) Nicoletta Di Ciolla; (a cura di) Anna Pasolini; (a cura di) Nicoletta Vallorani (Altre Modernità, 2016)
La finzione della legge. Crimine, giustizia, fatti e finzione.